Art Collection preservation: Gama-radiation application for decontaminating objects in the Instituto de Estudos Brasileiros - Rela, Paulo Roberto; Gomes, Fátima Faria; Thomé, Lúcia Elena; Kodama, Yasko (Revista do Instituto de Estudos Brasileiros, 2008)
The Instituto de Estudos Brasileiros (IEB) from the University of São Paulo received the charge from São Paulo's Federal Justice to take care of part of the collection from Banco Santos that was severely attacked by insects and micro-organisms (moulds) when stored in a warehouse that was flooded by intense rainfall. A chemical treatment to eliminate the biodeteriorating agents was tried but it was not effective. As the heap has a large amount of Xylograph wood dye, printings and manuscripts from cordel literature an urgent way to treat was searched and after the study and previous experience on wood irradiation process it was decided to submit promptly the heap to gamma irradiation. After the treatment the peaces were restored by IEB staff and now is being part of IEB collection and available for the scientific research community.